Sovereign bond market integration: the euro, trading platforms and globalization - Guntram B. Wolff; Alexander Schulz (Deutsche Bundesbank, 2008)
We disentangle different driving factors of sovereign bond market integration by studying yield co-movements of EMU countries, the UK, the US and 16 German Länder in the last 15 years. At a low frequency of weeks, bond market integration has increased gradually in the course of the last 15 years in EMU countries, as well as the UK, the US and the German Länder. The euro, as well as increasing international capital flows, appear to drive low frequency integration. In contrast, yield adjustments to changes of the German benchmark bond at high frequencies, i.e., 2 days, remain relatively low until October 2000, when a sharp increase in integration can be observed in all samples. The increase in high frequency integration can be attributed to electronic trading platforms becoming functional. The change-over from national currencies to the euro can not explain the dramatic increase in high frequency integration.
Keywords: E42; E44; F33; F37; G15; 330; sovereign bond market; bond market integration; EMU; electronic trading; Rentenmarkt; Öffentliche Anleihe; Internationaler Finanzmarkt; Marktintegration; Rendite; Internationaler Preiszusammenhang; EU-Staaten; USA; Großbritannien; Deutschland